Voting System for Ssg in Bestlink College of the Philippines for Senior High School: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Voting systems, including information on how to vote and the different types of voting systems.It needs careful planning and the close collaboration of numerous key personnel within thecompany. The created system will make voting easier.The problems encountered last year by the user were the flying voters, and the students didn’tknow who the people they voted for were; the researchers came up with the ideas and theright codes to fix the problem. The researcher, therefore, concluded that the system is ready tobe released and sold to Bestlink College of the Philippines.A manual voting system is widely used when it comes to elections. After writing in the ballotpaper, the ballots are ready to drop inside the ballot box or, in another way, using anautomated machine to organize and count all papers properly because the manual electionhas a long process of counting. With this system, human work can be reduced. We needed tomake a proper, traditionally systematic voting system.
Keywords: IT & Management